Examining the impact of modern teaching technology and foreign language training methods in Kazakhstan’s elementary schools - Kalbergenova, Sholpan; Lebedeva, Larissa; Ageyeva, Larissa; Uaidullakyzy, Elmira; Gafurova, Mahfuza (Journal of Education and e-Learning Research, 2026)
Kazakhstan officially recognizes the early learning of a foreign language. Young students must still adjust to their new language environment when they begin studying a new school subject in the second grade as a foreign language. The use of modern technologies will provide favorable conditions for successfully mastering the necessary knowledge in the classroom and overcoming obstacles. In this regard, it is critical to identify key teaching strategies that promote English language learning. The study aims to evaluate modern foreign language teaching technologies and their effects on developing young students' positive attitudes and motivation towards learning English. For this purpose, EG (n = 110) and CG (n = 100) were identified in which pre-experimental and post-experimental activities were carried out. The study revealed that some of the children in the group lack motivation to learn English. The teacher only uses foreign-language texts from textbooks. Other texts are not used in the classroom that students might find interesting. Students' vocabulary in monologues and dialogic speech is monotonous and does not correspond to their age or accepted speech norms. The traditional approach to teaching English in primary school does not fully address many existing issues. The study's findings demonstrated that the integration of modern teaching technology and training methods into classrooms increases young students' positive attitudes and motivation to learn English.